Research of molecular mass of proteins, which obtained by different technological methods of the Candida fungi cells disintegration - Rybalkin, Mykola; Strelnikov, Leonid; Strilets, Oksana (ScienceRise: Pharmaceutical Science, 2017)
For the treatment of candidiasis, one of the most common diseases in the world, it is perspective to develop a subunit vaccine based on proteins and polysaccharides of Candida albicans and Candida tropicalis. The aim. Investigate the molecular weight of the proteins derived from the Candida albicans and Candida tropicalis fungal cells by various technological methods of separate disintegration. Material and methods. Different methods of disintegration were used in the study, namely ultrasound, rubbing with abrasive material and freezing-defrosting. Results and discussion. According to the results obtained, it was determined that in all cases, the proteins were represented by three fractions with a molecular weight of up to 10 kDa, a molecular weight of up to 75 kDa, a molecular weight of over 75 kDa, which in each case almost did not differ in quantitative content. It should be noted significant quantitative dominance of fractions of proteins with a molecular fraction of up to 75 kDa in compare with other fractions. Conclusion. All investigated methods of disintegration, namely ultrasound, rubbing with abrasive material and freezing-defrosting, provide synchronous separation of the same fractions of proteins of fungal cells of Candida albicans and Candida tropicalis